How do Natural Resource Abundance and Agriculture Affect Economic Growth in Guinea? - Camara, Mamoudou (International Journal of Economics and Financial Issues, 2023)
This article investigates the asymmetric effects of both natural resource abundance and agriculture on economic growth in Guinea (also known as Guinea Conakry). Using the nonlinear autoregressive distributed lag (NARDL) approach on annual data from Guinea over the period 1986-2020, the findings tend to suggest that natural resource abundance has a negative effect on economic growth while agriculture promotes economic growth. More precisely, the results show that an increase in natural resource rents leads to a decrease in GDP per capita in both the short and long run while a decrease in natural resource rents increases economic growth in the long run. Concerning agriculture, the results reveal that a positive shock in agricultural added value increases economic growth in both the short and long run while a negative shock in agricultural added value leads to a decrease in economic growth in both the short and long run.